Transformasi Nilai Adat Melayu dalam Ekesrp Hikayat Bayan Budiman - Nazhifa Fadila; Elmustian (LP2M UIN Abdul Muthalib Sangadji Ambon, 2025)
This study aims to reveal the transformation of Malay traditional values in Hikayat Bayan Budiman through an analysis of excerpts or text passages that reflect moral and cultural teachings. Excerpts are used as a basis for tracing how values such as loyalty, honor, wisdom, and respect for family are represented and undergo meaning processing in accordance with the social context of Malay society. The study employs a qualitative approach that includes content analysis and hermeneutics methods. Each excerpt is analyzed to see the process of transformation from traditional customs to a more dynamic and contextual meaning. The results show that the transformation of values in Hikayat Bayan Budiman is found in six excerpts that appear through the delivery of advice, character dialogues, and moral events that emphasize the importance of positive character and local wisdom. The use of excerpts strengthens clear textual evidence regarding the role of hikayat as a medium for both preserving and renewing values, so the results can be optimized for strengthening Malay culture today.